Effect of a multi-frequency counter-current S-type ultrasound pretreatment on the defatted corn germ protein: enzymatic hydrolysis, ACE inhibitory activity and structural characterization. Issue 9 (4th September 2019) - Musa, Abubakr; Gasmalla, Mohammed A. A.; Ma, Haile; Sarpong, Frederick; Wali, Asif; Awad, Faisal N.; Duan, Yuqing
Abstract : The effect of low-frequency ultrasound pretreatments on the properties and structure of the defatted corn germ protein (DCGP) are investigated. Abstract : In this work, a defatted corn germ protein (DCGP) was pretreated with single frequency ultrasound at 20 kHz (SFU) and multi-frequency ultrasounds (20, 28, 35 and 40 kHz) (MFU). The microstructures, morphology, amino acid content, degree of hydrolysis, protein hydrolysate concentration and angiotensin-converting enzyme (ACE) inhibitory activity of the DCGP hydrolysate were analyzed. The results showed that both SFU and MFU pretreatments increased the ACE inhibitory activity of the DCGP hydrolysate more than that observed for the traditional method. Also, the SFU pretreatment showed the highest ACE inhibitory activity of 54% in comparison with that of the DCGP hydrolysates obtained via the traditional and MFU pretreatment methods. The results of ultraviolet-visible (UV-Vis) spectroscopy, fluorescence spectroscopy, surface hydrophobicity studies, Fourier-transform infrared spectroscopy (FTIR), atomic force microscopy (AFM) and scanning electron microscopy (SEM) confirmed the extent of the changes that occurred in the microstructures and morphology of DCGP pretreated with SFU and MFU. The results also indicated that the hydrophobic amino acid concentration was comparably higher in DCGP pretreated with SFU and MFU than that in the DCG protein isolated via the traditional method.